DESIGNING SUMMER WEAR APPAREL BY USING KUTHAMPULLY KASAVU SAREES - Sasi, Gopika N; Sadhna, (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Kerala saree, sometimes referred to as the Kasavu saree in the region, is a moving representation of the rich cultural legacy ingrained in Kerala, India. These sarees, which are crafted by the expert craftspeople of the Devanga Chettiar group, which is based in Kuthampully, a small town in the Thrissur district, are the embodiment of centuries' worth of elaborate artistry and tradition. In the sleepy village of Kuthampully, which has a population of more than two thousand, there is an unflinching commitment to celebrating and preserving this ancient weaving heritage This study investigates the traditional Kasavu sarees and their contemporary applications through a mixed-methods approach, integrating both qualitative and quantitative research techniques. The design process involved sourcing raw materials from Kuthampully, creating prints with reactive dye and smudge techniques. This study not only preserves the heritage of Kasavu sarees but also demonstrates their adaptability in modern fashion, offering a sustainable and innovative integration of traditional textiles into contemporary Western-style garments. This sustainable approach to fashion is not just a trend but a way to inspire change in the industry.